The Persistence of Residential Segregation by Race, 1940 to 2010: The Role of Federal Housing Policy. Issue 1 (January 2021) - Abramovitz, Mimi; Smith, Richard J.
Has public policy shaped the persistence of residential segregation by race over time? Social Structures of Accumulation (SSA) theory, which explains major shifts in policy paradigms as a response to an economic crisis informs our analysis. We compare federal housing policy across two SSAs: the Keynesian period (1940–1970) characterized by welfare state expansion and the neoliberal period (1970–2010) marked by its contraction. Using the isolation index (a segregation measure), we track changes in the 20 Great Migration cities with the highest Southern-born Black population. Segregation rose steadily from 1940 to 1970s, plateaued at high levels from 1970 to 2010, but remained higher in 2010 than in 1940. Historical policy analysis reveals that regardless of the period, federal housing policy actively promoted residential segregation and underscores the urgency for social workers to mobilize for policy change.